Powering Implanted Devices Wirelessly Using Spider-Web Coil - Amal Ibrahim Mahmood; Sadik Kamel Gharghan; Mohamed A.A. Eldosoky; Ahmed M. Soliman (Journal of Techniques)
Implantable biomedical (IBM) systems and biomedical sensors can improve life quality, identify sickness, monitor biological signs, and replace the function of malfunctioning organs. However, these devices compel continuous battery power, which can be limited by the battery's capacity and lifetime, reducing the device's effectiveness. The wireless power transfer (WPT) technique, specifically magnetic resonator coupling (MRC), was utilized to address the limited battery capacity of IBMs. By using WPT–MRC, the device can obtain power wirelessly, thereby reducing the need for frequent battery replacements and increasing the device's potential. In this research, spider-web coil (S-WC) based MRC–WPT was conceived and carried out experimentally to enhance low-power IBM's rechargeable battery usage time. The presented S-WC–MRC–WPT design uses series–parallel (S–P) configuration to power the IBM. Both transmitter and receiver coils exhibit an operating oscillation frequency of 6.78 MHz. The paper reports on experiments performed in the laboratory to assess the performance of the proposed design in terms of output DC at three different resistive loads and transmission distances with alignment conditions among the receiver and the transmitter coils. Various transfer distances ranging from 10 to 100 mm were investigated to analyze the DC output current (Idc). Specifically, under a 30 V voltage source (VS) and a transfer distance of 20 mm, the DC output current was observed to be 330, 321, and 313 mA at resistive loads of 50, 100, and 150 Ω, respectively.